Use of a 2-year continuing professional development programme to change Japanese physicians’ attitudes to learning primary care: a qualitative study - Masato Matsushima; Yasuki Fujinuma; Masayasu Seki; Tatsuhiro Joki; Hideo Okonogi; Yasuhiko Miura; Iwao Ohno; Jun Hiramoto (BMJ Open)
Objective To evaluate changes in the learning attitudes of primary care physicians.Design Qualitative study through one focus group interview with the programme’s participants. Analysis of the focus group content using the Steps for Coding and Theorization method.Setting Japan.Participants Eight primary care physicians who completed a 2-year continuing professional development (CPD) programme using a problem-based learning (PBL) approach, focused on acquiring the skills needed to practise as primary care physicians in the community.Results Participants described positive changes in their attitudes and behaviours as a result of the training programme. These changes were grouped into three main themes: ‘changes in learning methods regarding medical practice’, ‘encounters with diverse perspectives and values, and confidence gained from those encounters’, and ‘showing one’s attitude towards learning and its influence on others’. The experienced practitioners participating in this study reported that the programme helped them apply their skills more broadly; for example, searching the literature for psychosocial aspects of practice and engaging more comfortably with diverse perspectives. They reported the positive impact of their learning on their coworkers.Conclusion A 2-year CPD programme using PBL can influence primary care physicians’ attitudes and learning-related behaviours. Further research is needed to determine which specific aspects of the programme are the most effective and whether the changes in attitudes and behaviours described affect patient care.